A reflective busbar and a method for manufacturing the same

By using metallurgical combination of an aluminum reflective layer and a copper substrate in photovoltaic modules and combining with a high light-transmitting protective film, the problems of high cost, low reflectivity and aluminum corrosion of reflective bus bar materials are solved, and the effects of reducing costs, increasing reflectivity and extending service life are achieved.

CN119789548APending Publication Date: 2025-04-08WUXI SVECK TECH

Patent Information

Application Number
CN202510021613.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In existing photovoltaic modules, the reflective bus bar material is high in cost, has low reflectivity, and aluminum is easily corroded when in contact with materials such as EVA, which affects the service life of the component.

Method used

Aluminum is used as the reflective layer, and metallurgical combination of the copper substrate and the aluminum reflective layer is formed to form a copper-aluminum composite belt, combined with a high-transmitting protective film, to improve the light reflectivity and service life of the reflective bus bar.

Benefits of technology

It significantly reduces the material cost of reflective bus bars, increases the reflectivity of reflective bus bars, extends the service life of photovoltaic modules, and solves the problem of aluminum corrosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119789548A_ABST
    Figure CN119789548A_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of photovoltaic modules, and specifically relates to a reflective busbar and a manufacturing method thereof. The reflective busbar includes a solder layer, a copper substrate, an aluminum reflective layer and a high-light-transmittance protective film. The bottom and both sides of the aluminum reflective layer are embedded in the interior of the copper substrate. The top surface of the aluminum reflective layer is covered with a high-light-transmittance protective film. The bottom surface of the copper substrate and the outside of the copper substrate on the side are covered with a solder layer. The high-light-transmittance protective film extends from the top surface of the aluminum reflective layer to the top surface of the copper substrate and is seamlessly connected to the solder layer. The top surface of the aluminum reflective layer of the side reflective busbar is an inclined surface, and the top surface of the aluminum reflective layer of the middle reflective busbar is a serrated structure. The reflective busbar of the present invention can improve the light reflectivity of the reflective busbar and improve the module power on the premise of significantly reducing the cost of the busbar material. At the same time, it can solve the corrosion problem caused by the contact between aluminum and materials such as EVA, and can stabilize the service life of the photovoltaic module.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photovoltaic components, and in particular relates to a reflective busbar and a manufacturing method thereof. Background Art

[0002] Reducing costs and increasing efficiency is always the goal pursued in the photovoltaic field. In recent years, the price of photovoltaic modules has dropped significantly, and the cost has been continuously reduced. In addition to the manufacturing cost of the battery cells themselves, the cost of auxiliary materials is also an important link in reducing costs. As one of the eight auxiliary materials, photovoltaic welding ribbons are mainly made of copper and tin. As the price of precious metals continues to rise, their costs are also gradually rising. Therefore, reducing prices by changing materials has become an important way.

[0003] The use of copper-aluminum alloy is a method that can significantly reduce the cost of solder strip materials. Some component manufacturers are trying to use copper-clad aluminum as a substitute for pure copper, but copper-clad aluminum materials also have their defects. First, the processing cost of copper-clad aluminum is relatively high, and excessive processing costs can greatly offset the cost reduction brought by the replacement of materials; second, copper-clad aluminum materials will still use a full tin plating process, the amount of solder used will not be reduced, and the cost reduction is limited. In addition, reflective flow strips are currently widely used to compensate for light sources. For example, patent CN114664973A mentions the use of copper-clad aluminum materials to manufacture combined reflective busbars. Its principle is basically the same as patent CN220732718U, except that it is changed to copper-clad aluminum materials. Both technologies have the same problems: 1. The full tin plating method is still used, and the tin-lead solder layer is used as the reflective material, but the reflectivity of the hot-dip tin-lead alloy is low, only about 70%. In addition, the busbar reflective structure used on both sides of the component in this technology also has shading areas and invalid areas, such as the attached Figure 1 and 2 As shown. Since the reflective busbars of this shape are placed on both sides of the component, it is only meaningful to reflect light in a single direction. However, no matter what the shape of the triangular pattern is, there will be a part of the area that cannot reflect light. The effective use area is basically less than 70%, so the overall reflection efficiency is not high and the light compensation intensity is greatly impaired.

[0004] There are also related technologies to improve it. For example, the patent CN118315461A uses copper-aluminum single-sided composite tape instead of pure copper, and uses aluminum as a reflective material. The advantage of this technology is that the copper-aluminum single-sided composite tape has a low processing cost and a cost advantage; the aluminum surface does not stick to tin, which can save solder on one side, and the cost reduction advantage is further expanded. However, this method also has its fatal flaws, that is, aluminum is an active metal and has a large potential difference with the copper base. If aluminum directly contacts the packaging material, such as EVA film, during long-term use, aluminum will react chemically with the acetate generated by EVA and will be quickly corroded. If the aluminum content in the composite tape is high, as the aluminum is gradually corroded, its conductivity will gradually decrease. In the end, the current carrying capacity is insufficient to support the normal transmission of the photocurrent, and the problem of wire melting and power attenuation will occur, which seriously affects the service life of the photovoltaic module. Summary of the invention

[0005] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a reflective busbar and a method for manufacturing the same. The reflective busbar of the present invention can improve the light reflectivity of the reflective busbar and the power of the module while significantly reducing the cost of the reflective busbar material. At the same time, it can solve the corrosion problem caused by the contact between aluminum and materials such as EVA, and stabilize the service life of the photovoltaic module.

[0006] In order to achieve the above technical objectives, the technical solution adopted by the embodiment of the present invention is: In the first aspect, an embodiment of the present invention provides a reflective busbar, comprising a solder layer, a copper substrate, an aluminum reflective layer and a high-light-transmittance protective film, wherein the bottom and both sides of the aluminum reflective layer are embedded in the interior of the copper substrate, the top surface of the aluminum reflective layer is covered with the high-light-transmittance protective film, the bottom surface and side surfaces of the copper substrate are covered with a solder layer, and the high-light-transmittance protective film extends from the top surface of the aluminum reflective layer to the top surface of the copper substrate and is seamlessly connected to the solder layer.

[0007] Furthermore, the top surface of the aluminum reflective layer is an inclined surface, and the inclination angle is θ, 0°<θ<45°.

[0008] Furthermore, the top surface of the aluminum reflective layer is a sawtooth structure, the top angle α of the sawtooth structure is 120°±5°, and the height is 35-40 μm.

[0009] Furthermore, the inclination angle θ of the top surface of the aluminum reflective layer satisfies the following condition: 17°≤θ≤25°.

[0010] Furthermore, the mass ratio of the copper substrate to the aluminum reflective layer is 4:6-6:4, and its resistance is equivalent to that of a pure copper-based welding strip of the same length. By adjusting the cross-sectional area of ​​the copper substrate and the aluminum reflective layer, the overall resistance is adjusted to be consistent with the pure copper-based resistance of the same length, ensuring that the current resistance of the photovoltaic module remains unchanged.

[0011] Furthermore, the high light transmittance protective film is made of UV resin or silicon-modified high light transmittance thermosetting resin.

[0012] In a second aspect, an embodiment of the present invention provides a method for manufacturing the reflective bus bar according to the first aspect, comprising the following steps: Step S1, preparing copper foil and aluminum foil of specified size in a soft state after annealing, wherein the width of the copper foil is 0.4-0.8 mm greater than the width of the aluminum foil; Step S2, cleaning the surfaces of the copper foil and the aluminum foil with a metal cleaning agent to remove surface oil and oxide layer, and then washing with water, adding a small amount of antioxidant during the washing, and blowing away excess water with compressed nitrogen to keep the surface of the material clean; Step S3, placing the aluminum foil on the copper foil by a positioning device, and leaving the wider part of the copper foil evenly on both sides of the aluminum foil; Step S4, metallurgically combining the aluminum foil and the copper foil by cold rolling, and at the same time rolling up the wide part of the copper foil by a wrapping structure to wrap the side edge of the aluminum foil; Step S5, annealing is performed under a protective atmosphere to eliminate work hardening and further diffuse the copper-aluminum metallurgical layer; Step S6, using a bevel roller to roll the substrate obtained in step S5 on the surface of the aluminum foil to form an inclination angle θ to obtain a side reflective bus bar, and using a pattern roller to press a serrated pattern on the surface of the aluminum foil to obtain a middle reflective bus bar; Step S7, completely annealing the side reflective busbars and the middle reflective busbars obtained in step S6 in a protective atmosphere at 500-550° C.; Step S8, performing flux treatment on the material obtained in step S7, and forming a solder layer on the surface of the copper foil through a tin furnace; Step S9, mechanically polishing the surface of the aluminum foil; Step S10: a high light transmittance adhesive film is applied on the surface of the aluminum foil by printing, with a film thickness of 3-5 μm, and then subjected to light curing or heat curing treatment to form a high light transmittance protective film.

[0013] Furthermore, the tensile strength of the soft copper foil after annealing in step S1 is 200-280 MPa, and the tensile strength of the aluminum foil is 75-95 MPa.

[0014] Furthermore, in step S5, the annealing temperature is 450-550° C., and the holding time is 1-3 minutes.

[0015] The technical solution provided by the embodiment of the present invention has the following beneficial effects: 1. The reflective busbar of the present invention uses aluminum as the reflective layer, has a high reflectivity, and can effectively improve the power of the component.

[0016] 2. The reflective busbar material of the present invention has low cost. Taking the copper-aluminum weight ratio of 5:5 as an example, its density is only 47% of pure copper, which means that for the same weight of welding strip, the copper-aluminum composite strip can produce 1 times more components, and the copper-aluminum composite strip itself is inexpensive, and the cost reduction advantage is very obvious.

[0017] 3. The side reflective busbar of the present invention has a simple structure, high processing efficiency, and almost no shielding area, and the effective reflective area is maximized.

[0018] 4. The reflective busbar of the present invention solves the problem of local aluminum leakage that is prone to occur during the stretching process of copper-clad aluminum bars, and also avoids the risk of reduced reliability caused by the easy corrosion of aluminum in conventional copper-aluminum composite strips. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a structural schematic diagram of a side reflective busbar in the prior art.

[0020] Figure 2 It is a schematic diagram of the structure of another side reflective busbar in the prior art.

[0021] Figure 3 It is a schematic diagram of the structure of the side reflective bus bar of Example 1 of the present invention.

[0022] Figure 4 It is a schematic diagram of the structure of the middle reflective bus bar in Example 2 of the present invention.

[0023] Figure 5 yes Figure 3 and Figure 4 Schematic diagram of the application structure of the reflective busbar.

[0024] Explanation of the reference numerals: 1 - solder layer; 2 - copper substrate; 3 - aluminum reflective layer; 4 - high light transmittance protective film; 5 - side reflective bus bar; 6 - middle reflective bus bar; 7 - battery; 8 - upper glass plate; 9 - back plate. DETAILED DESCRIPTION

[0025] In the description of the present invention, it is necessary to understand that the directions or positional relationships indicated by directional words such as "inside, outside", "up, down", "left, right", etc. are usually based on the directions or positional relationships shown in the drawings. They are only for the convenience of describing the present invention and simplifying the description. Unless otherwise specified, these directional words do not indicate or imply that the device or element referred to must have a specific direction or be constructed and operated in a specific direction. Therefore, they cannot be understood as limiting the scope of protection of the present invention.

[0026] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0027] Example 1 A side reflective busbar includes a solder layer 1, a copper substrate 2, an aluminum reflective layer 3 and a high-light-transmittance protective film 4. The bottom and both sides of the aluminum reflective layer 3 are embedded in the copper substrate 2. The top surface of the aluminum reflective layer 3 is covered with the high-light-transmittance protective film 4. The bottom surface of the copper substrate 2 and the outer surface of the copper substrate on the side are covered with the solder layer 1. The high-light-transmittance protective film 4 extends from the top surface of the aluminum reflective layer 3 to the top surface of the copper substrate 2 and is seamlessly connected to the solder layer 1. The solder layer 1 is a solder layer, which plays the role of welding and protecting the copper substrate.

[0028] like Figure 3 As shown, the top surface of the aluminum reflective layer 3 is a slope with an inclination angle of θ, 0°<θ<45°, θ can be 5°, 10°, 13°, 15°, 17°, 19°, 21°, 23°, 25°, 27°, 29°, etc. The reflectivity at different angles θ is shown in Table 1 below.

[0029] Table 1 Reflectivity of aluminum reflective layer at different θ

[0030] It can be seen from Table 1 that when 17°≤θ≤25°, the reflective effect is better. When θ=21°, since there is no structure to block the light, the light utilization rate can reach up to 86.3%, which is significantly improved compared with the sawtooth reflective structure.

[0031] The mass ratio of the copper substrate 2 to the aluminum reflective layer 3 is 4:6-6:4.

[0032] The high light-transmittance protective film 4 is made of UV resin or silicon-modified high light-transmittance thermosetting resin.

[0033] Example 2 An intermediate reflective busbar includes a solder layer 1, a copper substrate 2, an aluminum reflective layer 3 and a high-light-transmittance protective film 4. The bottom and both sides of the aluminum reflective layer 3 are embedded in the copper substrate 2. The top surface of the aluminum reflective layer 3 is covered with the high-light-transmittance protective film 4. The bottom surface and the side surface of the copper substrate 2 are covered with a solder layer 1. The high-light-transmittance protective film 4 extends from the top surface of the aluminum reflective layer 3 to the top surface of the copper substrate 2 and is seamlessly connected to the solder layer 1. The solder layer 1 is a solder layer, which plays a role in welding and protecting the copper substrate.

[0034] like Figure 4 As shown, the top surface of the aluminum reflective layer 3 is a sawtooth structure, the top angle α of the sawtooth structure is 120°±5°, and the height is 35-40 μm.

[0035] The mass ratio of the copper substrate 2 to the aluminum reflective layer 3 is 4:6-6:4.

[0036] The high light-transmittance protective film 4 is made of UV resin or silicon-modified high light-transmittance thermosetting resin.

[0037] The UV resin in Example 1-2 uses Lencol L-6055 modified pure acrylic UV resin or Lencol L-8400A modified polyurethane acrylic UV resin; the silicon-modified resin uses SIC 6164F silicon-modified resin.

[0038] In Example 1-2, the mass ratio of the copper substrate 2 to the aluminum reflective layer 3 is 4:6-6:4, and its resistance is equivalent to that of a pure copper-based welding strip of the same length. By adjusting the cross-sectional area of ​​the copper substrate 2 and the aluminum reflective layer 3, the overall resistance is adjusted to be consistent with the pure copper-based resistance of the same length, ensuring that the current resistance of the photovoltaic module remains unchanged and that power loss due to increased resistance does not occur. All substrates of all specifications or mass ratios in the embodiments of the present invention follow this premise. The volume ratio of the copper substrate 2 and the aluminum reflective layer 3 and the ratio of the total volume to the pure copper reflective busbar of the same resistance meet the requirements of Table 2 below: Table 2 Conductivity and volume of copper substrate and aluminum reflective layer at different mass ratios

[0039] Note: The conductivity is the ratio of the conductivity of the pure copper welding strip with the same resistance. The volume of the same resistance is also the ratio of the volume of the pure copper reflective busbar with the same resistance. The sum of the mass fractions of copper and aluminum is 100%.

[0040] In Table 2, although the volume of the pure copper welding strip under the same resistance is more than 30% higher than the volume of the copper substrate and aluminum reflective layer in the embodiment of the present invention, due to the difference in density and price of copper and aluminum, the cost of the reflective busbar of the present invention is lower than that of the pure copper reflective busbar. Taking the copper-aluminum weight ratio of 5:5 as an example, its density is only 47% of pure copper, which means that for the same weight of welding strip, the copper-aluminum composite strip can produce 1 times more components, and the copper-aluminum composite strip itself is low in price, and the cost reduction advantage is very obvious.

[0041] Example 3 The manufacturing method of the reflective busbar comprises the following steps: Step S1, preparing copper foil (tensile strength of 250±5MPa) and aluminum foil (tensile strength of 80±5MPa) of specified size and in a soft state after annealing, wherein the width of the copper foil is 0.6mm larger than that of the aluminum foil; Step S2, cleaning the surfaces of the copper foil and the aluminum foil with a metal cleaning agent to remove surface oil and oxide layer, and then washing with water, adding a small amount of antioxidant during washing, and blowing away excess water with compressed nitrogen to keep the surface of the material clean; when cleaning with a metal cleaning agent, organic acid and surfactant will remain on the surface of the copper foil and the aluminum foil, and the above residues can be washed away by washing with water, and adding an antioxidant can prevent the surface of the copper foil and the aluminum foil from being oxidized; Step S3, placing the aluminum foil on the copper foil by a positioning device, and leaving the wider part of the copper foil evenly on both sides of the aluminum foil; Step S4, metallurgically combining the aluminum foil and the copper foil by cold rolling, and at the same time rolling up the wide part of the copper foil by a wrapping structure to wrap the side edge of the aluminum foil; Step S5, annealing is performed under a protective atmosphere to eliminate work hardening and further diffuse the copper-aluminum metallurgical layer; Step S6, using a bevel roller to roll the substrate obtained in step S5 on the surface of the aluminum foil to form an inclination angle θ to obtain a side reflective bus bar 5, and using a pattern roller to press a serrated pattern on the surface of the aluminum foil to obtain a middle reflective bus bar 6; Step S7, completely annealing the side reflective welding strip and the middle reflective welding strip obtained in step S6 at 525° C. in a protective atmosphere to obtain the mechanical properties required for the photovoltaic welding strip; Step S8, performing soldering treatment on the material obtained in step S7, and forming a solder layer 1 on the surface of the copper foil through a tin furnace; Step S9, mechanically polishing the surface of the aluminum foil of the welding strip; Step S10: a high light transmittance adhesive film is printed on the surface of the aluminum foil, with a film thickness of 3-5 μm, and a high light transmittance protective film 4 is formed by light curing or heat curing. The high light transmittance protective film 4 is made of SIC 6164F silicon modified resin.

[0042] Example 4 The schematic diagram of the application structure of the side reflective bus bar of Example 1 and the middle reflective bus bar of Example 2 is shown in Figure 5 As shown, where θ = 21° and α = 120°.

[0043] Comparative Example 1 Different from the fourth embodiment, the side reflective busbars are Figure 1 The structure of i =22°, β i =90°.

[0044] Comparative Example 2 Different from Example 4, the aluminum reflective layer in the side reflective busbars and the middle reflective busbar is replaced by tin-lead solder (the mass fraction of tin in the tin-lead solder is 60% and the mass fraction of lead is 40%).

[0045] Comparative Example 3 Different from the fourth embodiment, no high light transmittance protective film is provided in the side reflective bus bars and the middle reflective bus bars.

[0046] All comparative tests were conducted using 182mm monocrystalline silicon cells, 60 panels, and 450W modules, with comparisons made using modules using equivalent resistance pure copper-based conventional bus bars.

[0047] The power improvement of the components in Example 4 and Comparative Examples 1-2 relative to conventional components is shown in Table 3.

[0048] Table 3 Power improvement of Example 4 and Comparative Examples 1-2 relative to conventional photovoltaic modules

[0049] It can be seen from Table 3 that the average power of the photovoltaic modules in Example 4 and Comparative Examples 1-2 is improved to a certain extent compared with the average power of conventional photovoltaic modules, but the power improvement of Example 4 is more obvious compared with Comparative Examples 1 and 2.

[0050] The power attenuation and appearance changes of the DH2000 components in Example 4 and Comparative Example 3 after testing are shown in Table 4.

[0051] Table 4 Power attenuation and appearance changes of photovoltaic modules DH2000 after testing of Example 4 and Comparative Example 3

[0052] It can be seen from Table 4 that the power attenuation of the photovoltaic module in Example 4 after DH2000 test is much smaller than that in Comparative Example 3, and the appearance of the module in Example 4 does not change, while in Comparative Example 3, tiny bubbles appear in the EVA above the module welding strip, and there are slight corrosion spots at the copper-aluminum junction, which indicates that the high-light-transmittance protective film can reduce the power attenuation caused by corrosion of the aluminum reflective layer.

[0053] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A reflective bus bar, characterized in that: The invention comprises a solder layer (1), a copper substrate (2), an aluminum reflective layer (3) and a high-light-transmittance protective film (4), wherein the bottom and both sides of the aluminum reflective layer (3) are embedded in the copper substrate (2), the top surface of the aluminum reflective layer (3) is covered with the high-light-transmittance protective film (4), the bottom surface and the side surfaces of the copper substrate (2) are covered with a solder layer (1), and the high-light-transmittance protective film (4) extends from the top surface of the aluminum reflective layer (3) to the top surface of the copper substrate (2) and is seamlessly connected to the solder layer (1).

2. The reflective bus bar according to claim 1, characterized in that: The top surface of the aluminum reflective layer (3) is an inclined surface with an inclination angle of θ, 0°<θ<45°.

3. The reflective bus bar according to claim 1, characterized in that: The top surface of the aluminum reflective layer (3) is a sawtooth structure, the top angle of the sawtooth structure is α=120°±5°, and the height is 35-40 μm.

4. The reflective bus bar according to claim 2, characterized in that: The top surface inclination angle θ of the aluminum reflective layer (3) satisfies the following condition: 17°≤θ≤25°.

5. The reflective bus bar according to claim 1, characterized in that: The mass ratio of the copper substrate (2) to the aluminum reflective layer (3) is 4:6-6:4, and its resistance is equivalent to that of a pure copper-based welding strip of the same length. By adjusting the cross-sectional area of ​​the copper substrate (2) and the aluminum reflective layer (3), the overall resistance is adjusted to be consistent with the pure copper-based resistance of the same length, thereby ensuring that the current loss of the photovoltaic module remains unchanged.

6. The reflective bus bar according to claim 1, characterized in that: The high light transmittance protective film (4) is made of UV resin or silicon-modified high light transmittance thermosetting resin.

7. The method for manufacturing the reflective busbar according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step S1, preparing copper foil and aluminum foil of specified size in a soft state after annealing, wherein the width of the copper foil is 0.4-0.8 mm greater than the width of the aluminum foil; Step S2, cleaning the surfaces of the copper foil and the aluminum foil with a metal cleaning agent to remove surface oil and oxide layer, and then washing with water, adding a small amount of antioxidant during the washing, and blowing away excess water with compressed nitrogen to keep the surface of the material clean; Step S3, placing the aluminum foil on the copper foil by a positioning device, and leaving the wider part of the copper foil evenly on both sides of the aluminum foil; Step S4, metallurgically combining the aluminum foil and the copper foil by cold rolling, and at the same time rolling up the wide part of the copper foil by a wrapping structure to wrap the side edge of the aluminum foil; Step S5, annealing is performed under a protective atmosphere to eliminate work hardening and further diffuse the copper-aluminum metallurgical layer; Step S6, using a bevel roller to roll the substrate obtained in step S5 on the surface of the aluminum foil to form an inclination angle θ to obtain a side reflective bus bar (5), and using a patterned roller to press a serrated pattern on the surface of the aluminum foil to obtain a middle reflective bus bar (6); Step S7, completely annealing the side reflective busbars (5) and the middle reflective busbars (6) obtained in step S6 in a protective atmosphere at 500-550° C.; Step S8, performing a soldering treatment on the material obtained in step S7, and forming a solder layer (1) on the surface of the copper foil through a tin furnace; Step S9, mechanically polishing the surface of the aluminum foil; Step S10, coating the surface of the aluminum foil with a high light transmittance adhesive film by printing, with a film thickness of 3-5 μm, and subjecting the film to light curing or heat curing treatment to form a high light transmittance protective film (4).

8. The method for manufacturing a reflective bus bar according to claim 7, characterized in that: The tensile strength of the soft copper foil after annealing in step S1 is 200-280 MPa, and the tensile strength of the aluminum foil is 75-95 MPa.

9. The method for manufacturing a reflective bus bar according to claim 7, characterized in that: In step S5, the annealing temperature is 450-550° C., and the holding time is 1-3 minutes.

Citation Information

Patent Citations

  • Reflective bus bar, reflective bus bar assembly and battery assembly

    CN220732718U

Cited By

  • Gap film and photovoltaic module

    CN121310720A

  • Polishing and printing integrated equipment for reflective slope of photovoltaic bus bar

    CN224240643U